Selecting the Best Eyelid Techniques - Bayrak, Sinehan B.; Kriet, John D.; Humphrey, Clint D. (Facial Plastic Surgery, 2018)
The periorbital region is a focal point on the face. Dermatochalasis, fat herniation, blepharoptosis, brow ptosis, deep tear troughs, and malar fat pad descent are all age-related changes that occur around the eyes, and successful rejuvenation involves addressing all of these changes. Restoring a youthful, vibrant appearance to the eyes and periorbital areas can often only be accomplished with a combination of surgical and nonsurgical interventions. Facial plastic surgeons should have a comprehensive knowledge of all of these options and their applications to ensure good patient outcomes and satisfaction.
Keywords: periorbital rejuvenation; facial rejuvenation; blepharoplasty; browlifting; eyelid